Assessment of biodiversity and conservation status of flora and fauna in Madiun City, East Java, Indonesia - OKID PARAMA ASTIRIN; FETRIA WIDIYANTI; SURATMAN SURATMAN; NUGROHO ANDI PURNOMO; M. ARIF ROMADLON; HADI WIWIT HENDRO CAHYONO; DIAGAL WISNU PAMUNGKAS; WIDYA MEGA RAHMAWATI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Astirin OP, Widiyanti F, Suratman, Purnomo NA, Romadlon MA, Cahyono HWH, Pamungkas DW, Rahmawati WM. 2025. Assessment of biodiversity and conservation status of flora and fauna in Madiun City, East Java, Indonesia. Biodiversitas 26: 3965-3972. Madiun City in East Java, Indonesia is a small municipality that has evolved into an urban center due to its strategic position as the hub of socio-economic activities, including trade, industry, and healthcare. Urbanization in the town poses a threat to biodiversity. This is due to changes in land use and cover, natural exploitation, introduction of exotic species, air and water pollution, and climate change. This study aims to explore biodiversity in Madiun City to inform the development of strategies and policies for natural resource management. The observations revealed that Madiun City is home to 122 tree species, 76 species of ornamental plants, and 143 species of animals, including mammals, birds, reptiles, amphibians, fish, and insects. Eight plant species and five animal species are listed in the IUCN Red List. Additionally, there are eight plants and five animals listed under CITES, as well as six animals listed as protected under the Indonesian Ministry of Environment and Forests' P106/2018. Leucopsar rothschildi, Padda oryzivora, and Pavo muticus are birds listed under all the three protection instruments, suggesting their conservation importance. Green open spaces with aviaries are crucial for conserving biodiversity, as they offer a range of ecological, aesthetic, social, and economic benefits. Community participation with the local government is vital to conservation programs in urban areas. Active community involvement in conservation programs and socialization can significantly support the success of biodiversity conservation.